Does Frequency of Audits Improve Taxpayer Compliance? - Sor Tin, Saw (2017)
The purpose of this study is to find out whether frequency of audits can improve taxpayer compliance and show how the findings can impact policymakers’ decision and tax agencies’ future strategic action plan. It then offers some useful suggestions for improving compliance and reducing tax gap. The first test result shows a significant difference in number of times audited among the taxpayers. The Group Mean is distinctly found to be higher among those who have undergone ‘second or fourth audit’ compared to those with ‘first or third audit’. The final analysis indicates a nonlinear relationship between audit frequency and tax compliance. This case study finds that changes in taxpayer compliance have followed a cyclical pattern; and frequency of audits may improve taxpayer compliance depending on the compliance cycle. It is thus concluded that future tax audit strategic plan should focus on effective approaches to ensure a higher level of compliance after an audit in order to reduce time and costs incurred by business entities or tax authority during subsequent audits